1985
DOI: 10.1111/j.1574-6968.1985.tb01181.x
|View full text |Cite
|
Sign up to set email alerts
|

Metal resistance in bacteria

Abstract: Bacteria have been examined that have developed very efficient and different mechanisms for tolerating heavy metals. Often normal toxic levels of metals have no effect on cell growth of resistant strains. In many organisms, the genes controlling metal resistance are carried on plasmids, which provide the bacteria with a competitive advantage over other organisms when metals are present. Not all metal-resistant bacteria contain plasmids. For example, a Pseudomonas sp. (research at the Canada Centre for Inland W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
2

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(70 citation statements)
references
References 68 publications
5
61
0
2
Order By: Relevance
“…Actually, high diversity and evenness seemed to be common features in marine microbial communities of many chemically polluted environments (9), probably because pollution disturbance generated conditions for the proliferation of rare taxa with stress resistance. According to the widely reported metal resistance of bacteria (38)(39)(40), the acute response of the bacterial community to the higher Cd levels at the early stage might be due to the proliferation rate of resistant taxa being higher than the extinction rate of sensitive taxa. However, this trend disappeared later, indicating that the temporal succession overwhelms Cd-induced patterns in the alpha diversity of bacterial community.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, high diversity and evenness seemed to be common features in marine microbial communities of many chemically polluted environments (9), probably because pollution disturbance generated conditions for the proliferation of rare taxa with stress resistance. According to the widely reported metal resistance of bacteria (38)(39)(40), the acute response of the bacterial community to the higher Cd levels at the early stage might be due to the proliferation rate of resistant taxa being higher than the extinction rate of sensitive taxa. However, this trend disappeared later, indicating that the temporal succession overwhelms Cd-induced patterns in the alpha diversity of bacterial community.…”
Section: Discussionmentioning
confidence: 99%
“…This type of pedogenesis results in 1.2-2.0 mg nickel per gram soil dry weight in nickel-rich serpentine soils (Mengoni et al 2001). Here, we isolated the strain Tosca3, displaying the most pronounced resistance (for calculating concentration of resistance see Duxbury 1981;Trevors et al 1985), from the ultramafic soil sample of Tuscany. There are only very few studies on antimicrobial characteristics of isolates originating from this type of soil.…”
Section: Metal Resistance and Bioactivity Of Strains From Contaminatementioning
confidence: 99%
“…Mercury resistance has been extensively investigated and reviewed by numerous researchers (Foster, 1983;Robinson & Tuovinen, 1984;Brown, 1985;Trevors et al, 1985). Mercuryresistant bacteria have also been isolated from numerous environments including sediment samples .…”
Section: Mercurymentioning
confidence: 99%
“…This problem is also complicated by the various forms of metals used, and the influence that complexing agents and environmental conditions have on the availability and form of the metals. For a review of this problem with examples of metal concentrations found in the literature, the reader is referred to a review by Trevors et al (1985).…”
Section: Mercurymentioning
confidence: 99%